A room of one's own - Woolf, Virginia, 1882-1941.; Bradshaw, David, 1955-; Clarke, Stuart Nelson (Malden, MA : John Wiley/Blackwell, 2015)
A Room of One's Own, is one of Virginia Woolf's most influential works and is widely recognized for its extraordinary contribution to the women's movement. This timely and important new edition adopts the complete text of the first British edition published in 1929. Features a comprehensive introduction detailing the process and composition of Woolf's original essay and the evolution of its subsequent publication history The first comprehensive and authoritative edition of this foundational text of the feminist movement, and one of the most significant works in Woolf's own canon The only.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Woolf, Virginia, -- 1882-1941 -- Authorship; Literature -- Women authors -- History and criticism -- Theory, etc; Women and literature -- Great Britain; Women authors -- Economic conditions; Women authors -- Social conditions; Authorship -- Sex differences; Authorship -- Sex differences; Literature -- Women authors -- History and criticism -- Theory, etc; Women and literature -- Great Britain; Women authors -- Economic conditions; Women authors -- Social conditions; Woolf, Virginia, 1882-1941 -- Authorship; Electronic books; Electronic books